Performance analysis of integrated cellular and ad hoc networks system in the dead spots - LU Wei-feng; WU Meng (Tongxin xuebao)
A new architecture of integrated cellular and ad hoc networks system in the dead spots was introduced,and the system’s relay-availability probability under this environment was analyzed.Then by combining with the relay-availability probability,build the analytical model of integrated cellular and ad hoc networks system,and based on this model,get the call dropping probability of the traditional cellular system and integrated cellular and ad hoc networks system respectively by mathematical analyzing.Finally,through numerical simulation,compare the two kinds of system’s performance under the environment of dead spots,and analyze the impact of the various parameters on the integrated cellular and ad hoc networks system’s performance.